“SAVE WATER, SAVE JAKARTA” CAMPAIGN AS LAND SUBSIDENCE MITIGATION IN JAKARTA - Jihadi, Luthfan Harisan; Ali, Abu Abdillah; Zakaria, Zufialdi; Anural, Muhammad Bey (Bulletin of Scientific Contribution, 2014)
Jakarta, a very populated capital city of Indonesia, was built above alluvial deposit which is currently subsiding relative to sea level at a high rate. As a result Jakarta becomes more often to be flooded with water that delivered from other regions and also the sea level rises relative to land and shoreline move toward the ground are increasing feasibility of tidal flood to occur. Consolidation process of the ground acts as a cause to the land subsidence in Jakarta. The fact is water needs in Jakarta is high due to its high population. Therefore, large amount in withdrawal of groundwater occurs and causes the ground to settle. In order to decrease the rate of land subsidence, groundwater should be extracted in a proper, more effective and efficient way. Younger generation is advised to save water using a fresh approach which is easy to be understood and accepted. In the future, people in Jakarta will consider that saving water as a norm which brings great benefit to their environment, Jakarta.